Cryopreservation of ovarian tissue: detailed description of methods for transport, freezing and thawing - Isachenko, Vladimir; Montag, Markus (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: In many cases cancer therapy leads to an irreversible reduction or even loss of ovarian reserve. Cryopreservation of ovarian tissue with subsequent thawing and re-transplantation of tissue after the cancer is in remission constitutes a promising method to preserve fertility in women. To date, more than 25 cases of live births after re-transplantation of cryopreserved ovarian tissue have been published worldwide. In Germany the first live birth after re-transplantation of cryopreserved tissue was in 2011. Material and Methods: After surgical removal of ovarian tissue in the Gynaecological Clinic of Dresden University, the tissue was sent to the Gynaecological Clinic of Bonn University in a special transport container at 5 °C and was frozen the next day using 1.5 M dimethyl sulfoxide cryosolution. In 2010 this ovarian tissue was thawed using a sucrose solution in the Gynaecological Clinic of Erlangen University Clinical Centre and was laparoscopically re-transplanted into the patient. Results: The patient became pregnant, the pregnancy was uneventful, and she gave birth to a healthy boy. Conclusion: Freezing of ovarian tissue with subsequent re-transplantation as described here is a viable method to preserve fertility in cancer patients.
Gesehen am 21.11.2018